Magnetic theranostics of Lewis lung carcinoma with the complex of gadopentetate dimeglumine and doxorubicin - Orel, V. E.; Rykhalskyi, O. Yu.; Golovko, T. S.; Ganich, O. V.; Romanov, A. V.; Orel, I. V.; Burlaka, A. P.; Lukin, S. N.; Venger, E. F. (Reports of the National Academy of Sciences of Ukraine, 2016)
The antitumor effect of the complex of gadopentetate dimeglumine (GD) and doxorubicin (DR) in mices with Lewis lung carcinoma is studied. It is shown that the breaking ratio of Lewis lung carcinoma growth was greatest for the group of animals treated with the complex of GD and DR and exposured to external local inhomogeneous static magnetic and electromagnetic fields. According to the computer analysis of magnetic resonance images, the administration of the complex and the electromagnetic irradiation (EI) of Lewis lung carcinoma resulted in a reduction of the tumor image area by 11.8 %, as compared to the officinal DR effect. The DR administration to the animals with Lewis lung carcinoma decreased the level of free iron in the mitochondria of tumor cells by 63 %, as compared to control tumors without influence; while the administration of the complex of GD and DR, on the contrary, increased the level of free iron 9 times, and it was increased by 88 % when combined with EI, as compared to the control group.